Tinjauan Aspek Keamanan dan Kerahasiaan di Ruang Penyimpanan Rekam Medis di RSUD Kota Depok - Shania Salsabillah; Daniel Happy Putra; Laela Indawati; Nanda Aula Rumana (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Security and confidentiality of medical records in the storage room is one of the supporting factors for the creation of confidentiality of patient medical record information, to get the expected results it is necessary to have medical records officers, medical records, storage rooms, SOP (Standard Operating Procedures) security and confidentiality in the medical record room, as well as facilities and facilities in the storage room. This research was conducted in the Medical Record Unit of the Depok City Hospital. This study aims to determine the aspects of security and confidentiality in the medical record storage room. This study uses descriptive analysis method with a qualitative approach by conducting interviews and observations. The research results obtained at the Depok City Hospital already have 2 standard operating procedures, namely regarding security and confidentiality and standard procedures for storing medical records. However, the implementation of the work has not been carried out optimally. There are medical records whose covers are damaged, not replaced with new ones, the medical record storage room still uses a manual door which in the standard procedure must use a coded key. This makes the implementation of work at the Depok City Hospital has not been carried out according to existing standard operating procedures. Supporting facilities in the storage room are also inadequate, especially for the second storage room which only has 1 air conditioner, does not have good ventilation for air exchange so that there is no air between stored medical records, does not have a temperature and humidity control device.